Audit Energi Sederhana Pada Pompa Distribusi IPA 2 Pramuka PAM Bandarmasih Kota Banjarmasin - Alvin Rahmadiar Alam; Adhi Yuniarto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In 2022, the energy cost of PT. Air Minum Bandarmasih Kota Banjarmasin will be Rp. 586/m3 while the national average energy cost was Rp. 363.45/m3. In 2023, IPA 2 Pramuka distributed 41,152,457 m3 at an energy cost of Rp. 479.13/m3. A key step in energy management is to conduct regular energy audits. Energy audits are conducted to assess pump efficiency and determine Specific Energy Consumption (SEC), which facilitates technical recommendations for energy management. The first results of the energy audit at the IPA 2 Pramuka distribution unit of PT. Air Minum Bandarmasih revealed a power factor (cos φ) of less than 0.85, which is detrimental to energy efficiency. The pump efficiency was 50-60%, indicating that minor pump adjustments were needed. In addition, the SEC in 2023 was slightly above 0.4 kWh/m3 (about 0.40094 kWh/m3). The proposed improvement measures were the repair of the pump and regular maintenance, as well as the installation of a capacitor bank to improve the energy efficiency of the distribution unit of IPA 2 Pramuka.